Apolipoprotein E associates with beta amyloid peptide of Alzheimer's disease to form novel monofibrils. Isoform apoE4 associates more efficiently than apoE3. - Sanan, D A (1994)
Late-onset and sporadic Alzheimer's disease are associated with the apolipoprotein E (apoE) type 4 allele expressing the protein isoform apoE4. Apolipoprotein E binds avidly to beta amyloid (A beta) peptide, a major component of senile plaque of Alzheimer's disease, in an isoform-specific manner. The apoE4 isoform binds to A beta peptide more rapidly than apoE3. We observed that soluble SDS-stable complexes of apoE3 or apoE4, formed by coincubation with A beta peptide, precipitated after several days of incubation at 37 degrees C with apoE4 complexes precipitating more rapidly than apoE3 complexes. A beta(1-28) and A beta(1-40) peptides were incubated in the presence or absence of apoE3, apoE4, or bovine serum albumin for 4 d at 37 degrees C (pH 7.3). Negative stain electron microscopy revealed that the A beta peptide alone self-assembled into twisted ribbons containing two or three strands but occasionally into multistranded sheets. The apoE/A beta coincubates yielded monofibrils 7 nm in diameter. ApoE4/A beta coincubates yielded a denser matrix of monofibrils than apoE3/A beta coincubates. Unlike purely monofibrillar apoE4/A beta coincubates, apoE3/A beta coincubates also contained double- and triple-stranded structures. Both apoE isoforms were shown by immunogold labeling to be uniformly distributed along the A beta peptide monofibrils. Monofibrils appeared earlier in apoE4/A beta than in apoE3/A beta in time-course experiments. Thus apoE3 and apoE4 each interact with beta amyloid peptide to form novel monofibrillar structures, apoE4 more avidly, a finding consistent with the biochemical and genetic association between apoE4 and Alzheimer's disease.